Design and implementation of a mobile app for the pharmacotherapeutic follow-up of patients diagnosed with immune-mediated inflammatory diseases: eMidCare - Romero-Jimenez, Rosa; Escudero-Vilaplana, Vicente; Chamorro-de-Vega, Esther; Ais-Larisgoitia, Arantza; Lobato-Matilla, Elena; Somoza-Fernández, Beatriz; Ruiz-Briones, Paula; González, Carlos; Baniandrés, Ofelia; Menchén, Luis; Lobo-Rodríguez, Carmen; Herranz, Ana; et al. (Frontiers in Immunology, 2022)
Background Pharmacotherapeutic management of immune-mediated inflammatory diseases (IMID) has become more complex due to the development of new treatments, such as biological therapies. Mobile health, especially apps, can provide IMID patients with greater autonomy and facilitate communication with healthcare professionals. Our objective was to design and implement an app for remote monitoring and communication with IMID patients. Methods A multidisciplinary group was created to design and develop an app for IMID patients in a tertiary hospital. The app functionalities were identified through a focus group with IMID patients and through an observational, descriptive study of available apps for IMID patients at App Store and Play Store platforms. Once the app was designed and developed, we offered the app to IMID patients who initiated a new biological therapy. The inclusion period was from December 2020 to August 2021. We performed an observational, longitudinal study to assess the app's impact on medication safety, communication, satisfaction, and usability. Results We designed an app (eMidCare®) with the following modules: My Medication, My Questionnaires, Adverse Events, Useful Information, Messages, and Patient Profile. A total of 85 patients were installed with the app. The median (range) follow-up time for app use was 123 (5-270) days. In the My Medication module, 100% of patients registered their biological therapy and 25.9% also used this module to record each dose of medication administered. A total of 82 adverse events (AEs) were registered. Thirty-two percent of the patients registered at least 1 AE. The most frequent AEs were fatigue, injection site reaction, headache, and nausea. Fifty-two percent of patients used the Messages module to communicate with healthcare professionals. The most frequent messages concerned doubts about managing AEs (26.2%) and drug interactions (18.9%). The satisfaction survey yielded a median (range) score of 9.1 (7-10) out of 10. Conclusions We developed an app, eMidCare®, which reminds patients to take their medication, enables them to record AEs, and helps them communicate with healthcare professionals. Approximately one-third of the patients registered the administration of the biological therapies and registered at least 1 AE. The most used and most satisfactory functionality was communication with professionals.